Developing critical literacy in science through an SFL-informed pedagogical heuristic. Issue 1 (8th April 2019) - Fang, Zhihui; Adams, Brittany; Gresser, Valerie T.; Li, Cuiying
Abstract : Purpose: This paper describes and exemplifies a pedagogical heuristic for promoting critical literacy in science. Design/methodology/approach: One way to support critical literacy in science is through a linguistically informed pedagogical heuristic called 5Es – Enquire, Engage, Examine, Exercise and Extend. Findings: This paper describes the implementation of 5Es in a four-week middle school science unit on climate change, showing how the heuristic can be used to develop students' understanding of the varied ways authors use language to present information, structure text, infuse judgment and evaluation, engage with and position the reader and express epistemic commitment to knowledge claims. Originality/value: 5Es offer teachers a new heuristic for text exploration that develops students' critical language awareness, advanced literacy and disciplinary literacy at the same time.